Probiotic Bacterium-Derived p40, p75, and HM0539 Proteins as Novel Postbiotics and Gut-Associated Immune System (GAIS) Modulation: Postbiotic-Gut-Health Axis - Feray Gençer Bingöl; Duygu Ağagündüz; Ferenc Budán (Microorganisms)
It is known that probiotics have direct and indirect effects on many systems in the body, especially the gastrointestinal system. Interest in using probiotic strain-derived cell components and metabolites has also increased as a result of the significant benefits of probiotics. Although many terminologies and definitions are used for these components and metabolites, the International Scientific Association of Probiotics and Prebiotics (ISAPP) recommended the use of the term postbiotic in 2021, which is defined as “a preparation of inanimate microorganisms and/or their components that confers a health benefit on the host”. Postbiotics are bioactive metabolites such as organic acids, peptides/proteins, cell wall components, functional enzymes, short-chain fatty acids, vitamins, and phenols. These molecules mediate many positive effects such as immunomodulatory, antimicrobial, and antioxidant effects. These positive effects on maintaining health have enabled the identification of many new postbiotic proteins such as p40, p75, and HM0539. In this review, the postbiotic proteins p40, p75, and HM0539 derived from lactobacilli and their functional effects are systematically summarized. The p40 protein, in particular, has been shown to support gut barrier activity and reduce inflammation, potentially through mechanisms involving epidermal growth factor receptor-dependent signaling. Additionally, p40 and p75 proteins exhibit protective effects on intestinal epithelial tight junctions, suggesting their therapeutic potential in preventing intestinal damage and diseases such as colitis. HM0539 enhances intestinal barrier integrity, exhibits antiinflammatory properties, and protects against bacterial infection, suggesting its possible as a therapeutic for inflammatory bowel disease. This review may contribute to future studies on the therapeutic use of p40, p75, and HM0539 postbiotic proteins in inflammatory gastrointestinal system diseases.